Nanofabrication with the thermal AFM metallic tip irradiated by continuous laser. Issue 179 (24th March 2017) - Cui, Jianlei; Zhang, Jianwei; Barayavuga, Theogene; Wang, Xuewen; He, Xiaoqiao; Yang, Lijun; Xie, Hui; Mei, Xuesong; Wang, Wenjun
ABSTRACT: Based on the near-field optical lithography with the metallic AFM tip irradiated by pulse laser, the nanofabrication is proposed with the thermal AFM tip irradiated by continuous laser. The corresponding electric and thermal fields are calculated and simulated to reveal the mechanism. With the thermal AFM tip, the nanostructures can be fabricated with the thermal melting and mechanical extrusion effects based on the thermal expansion effect of the metallic AFM probe.